2010
DOI: 10.3390/d2040610
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding for Honey Biodiversity

Abstract: Honey is produced by honeybees from nectar and from secretions of living plants. It reflects the honeybees’ diet and the local plant communities. Honey also shows different plant compositions in different geographical locations. We propose a new method for studying the plant diversity and the geographical origin of honey using a DNA barcoding approach that combines universal primers and massive parallel pyrosequencing. To test this method we use two commercial honeys, one from a regional origin and one compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 29 publications
1
76
0
Order By: Relevance
“…While plant identification from DNA has presented numerous challenges (CBOL 2009), it has the advantage of providing finer definition of species‐specific foraging preferences for plant families whose pollen is difficult to distinguish morphologically (Bell et al., 2016; Bruni et al., 2015; Hawkins et al., 2015; Kraaijeveld et al., 2015; Pornon, Andalo, Burrus, & Escaravage, 2017). DNA sequencing has been used successfully to identify the foraging preference of honeybees and the floral composition of their honey (Bruni et al., 2015; De Vere et al., 2017; Galimberti et al., 2014; Hawkins et al., 2015; Jain, Jesus, Marchioro, & Araújo, 2013; Valentini, Miquel, & Taberlet, 2010). Several studies have also used pollen DNA sequencing to identify solitary bee foraging preferences (Sickel et al., 2015; Wilson, Sidhu, Levan, & Holway, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While plant identification from DNA has presented numerous challenges (CBOL 2009), it has the advantage of providing finer definition of species‐specific foraging preferences for plant families whose pollen is difficult to distinguish morphologically (Bell et al., 2016; Bruni et al., 2015; Hawkins et al., 2015; Kraaijeveld et al., 2015; Pornon, Andalo, Burrus, & Escaravage, 2017). DNA sequencing has been used successfully to identify the foraging preference of honeybees and the floral composition of their honey (Bruni et al., 2015; De Vere et al., 2017; Galimberti et al., 2014; Hawkins et al., 2015; Jain, Jesus, Marchioro, & Araújo, 2013; Valentini, Miquel, & Taberlet, 2010). Several studies have also used pollen DNA sequencing to identify solitary bee foraging preferences (Sickel et al., 2015; Wilson, Sidhu, Levan, & Holway, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, removal of sugar from the honey samples will be important during the DNA extraction process. On the other hand, the high carbohydrate concentration in the honey helps DNA preservation, 11 as sugars stabilize nucleic acids, 12 and honey provides an airtight seal that prevents oxygen from entering and thus, preserving DNA from being degraded. 11 The presence of polyphenolic content makes the isolation of high-quality nucleic acids problematic; in addition, residual polyphenolics interfere in enzymatic reactions, such as PCR and endonuclease restriction digestion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the high carbohydrate concentration in the honey helps DNA preservation, 11 as sugars stabilize nucleic acids, 12 and honey provides an airtight seal that prevents oxygen from entering and thus, preserving DNA from being degraded. 11 The presence of polyphenolic content makes the isolation of high-quality nucleic acids problematic; in addition, residual polyphenolics interfere in enzymatic reactions, such as PCR and endonuclease restriction digestion. 13 In the present study, initial incubation of the sample dissolved in water resulted in removal of sugar and polyphenols as supernatants after the centrifugation process.…”
Section: Discussionmentioning
confidence: 99%
“…Several chemical methods were also proposed, such as aroma compounds, free amino acids or minerals and trace elements. Even if all these methods work well for identifying the geographic origins and for distinguishing honey with different botanical origins, they provide only limited information on the plant composition [51]. In fact, it is not always possibile to recognize individual species because some pollen is not well distinguishable by its morphological traits (e.g., Campulanaceae and Lamiaceae) [50].…”
Section: Use Of Dna Barcoding and Genetic Traceability Of Plant-derivmentioning
confidence: 99%
“…Recently, DNA barcoding was proposed as molecular tool for honey traceability exploitable in distinct steps of the supply chain. Some reserachers demonstrated that standard barcodes, such as trnL gene intron and rbcL gene region, are suitable for identifying plant traces from different honey samples, but anable for determining the botanical composition of individual honey species [50,51]. A synergism between multiple barcode markers among those conventionally used is in fact necessary to differentiate congeneric taxa.…”
Section: Use Of Dna Barcoding and Genetic Traceability Of Plant-derivmentioning
confidence: 99%